PENGARUH UKURAN FLY ASH PADA KEKUATAN BENDING KOMPOSIT RESIN EPOXY - Zamzami, Yusman; Savetlana, Shirley; Ibrahim, Gusri Akhyar (Jurnal Ilmiah Teknik Mesin FEMA, 2013)
Fly ash is one of the solid waste generated by industries that use coal as a fuel for the production process. Fly ash contains silica or alumina silica that has no adhesive properties (cementation) to himself. The purpose of this research was to determine the bending strength of composites reinforced fly ash (coal waste) through the bending test. In this study, fly ash was sieved with a sieve to obtain a variation of fly ash particle size of 40 mesh, 80 mesh and 120 mesh. Composite manufacturing using hand lay up with a mixture ratio of epoxy resin and hardener 1:1. Next step is mixing matrix and fly ash with mass fraction 60%: 40% use of fly ash particle size variation. Transform and then testing bending and for pure epoxy resin composites with various particle sizes. Photo fracture area with Scanning Electron Microscope (SEM) was used to analyze the causes of failure in composites. In this study the mechanical properties of the composite bending test in accordance with ASTM D790. The test results showed that the bending strength of the composite teringgi achieved with fly ash particle size of 120 mesh, the bending strength of 59.26 N/mm2 obtained. Factors that affect the bending strength is power tie fly ash particles with the matrix, the distribution and number of particles are evenly distributed in the composite particles. SEM image results in the fracture of composite particles of fly ash shows the tie between the matrix and the particles are quite good. Keywords: Fly ash, composite, bending strength